Image recognition-based dosage form dispensers (2021)
This invention provides a dosage form dispenser, comprising a casing comprising a first portion adapted for insertion within an oral cavity of a subject and a second portion adapted to encase a dosage form dispensing mechanism located therewithin; at least one camera positioned on said second portion of said casing, further positioned to capture a field of view of a portion of a face of a subject, wherein said field of view comprises at least a portion of a base view of the nose of said subject; a dosage form dispensing mechanism; a microprocessor and associated memory for processing and storing user authentication information, comparing images relayed from said at least one camera to at least one stored user standard and providing authentication when a match is established; and an interface connected to said dispensing mechanism, which promotes dispensing said dosage form when said authentication has been obtained. Methods for dispensing a dosage form directly within an oral cavity of a subject in need thereof, using the dispensers are also described.